Design of real-time co-simulation platform for wind energy conversion system - Bing Li; Haoran Zhao; Junchao Diao; Mingzhe Han (Energy Reports, 2020)
This paper presents an all-digital real-time co-simulation platform of refined Wind Energy Conversion System (WECS) model. The proposed platform is based on the Real-time Digital Simulator (RTDS) and FAST developed by National Renewable Energy Laboratory (NREL). The detailed generator and converter models are implemented in RTDS to simulate the electromagnetic transient. The models of wind, blade, tower, nacelle, and drivetrain are implemented in FAST to simulate the aerodynamic, structure, and turbulence dynamics. In such way, the designed co-simulation platform can capture all the dynamics, which can significantly enhance the simulation accuracy. Conventionally, RTDS and FAST communicate by the analogue signals, whose number of the exchanged data is quite limited. To overcome this limitation, the all-digital interface technique between RTDS and FAST is proposed. The correctness of the platform is verified by the simulation result.
Keywords: 330; FAST; Hardware-in-loop test; Multi-time scale; Real-time co-simulation; Refined model; RTDS